Displaying islamic arts in global cities - Correia, Jorge (2021)
There is an urgent need for a new conceptual cartography in museums that better reflects the cities hosting them. While many have gone global, institutions have encapsulated an enduring vision that remains, somehow, an orientalist gaze towards the lands of Islam. The time has come to foster a common path between the reality of the globalization of urban built environments and the display of Islamic arts